“Be War in Tyme, Approchis Neir the End”: The Sense of an Ending in the Testament of Cresseid - Ruszkiewicz, Dominika (Studia Anglica Posnaniensia, 2016)
The story of Troilus and Criseyde - whether in Chaucer’s or Henryson’s renditions - is not a story about a new beginning, but a story about an end: the end of love, of hope, and finally - the end of life: Troilus’s life in Chaucer’s poem and Cresseid’s life in Henryson’s. The Scottish version of the story, however, not only evokes the end of an individual life, but also the end of the world. The purpose of this paper is to situate Henryson’s poem in the context of apocalyptic fiction - fiction which is concerned with loss, decay and the finality of things. My contention that the poem belongs to the apocalyptic genre is based on a number of its features, such as the elegiac mood and imagery, the contrast between the past and the present, as well as the pattern of sin-redemption-preparation for death, which applies to Cresseid’s life, but also invites reflection on our own.